PEDAGOGICAL SUPPORT OF BACHELOR'S PROFESSIONAL SELF-DETERMINATION - Elena Yu. Valitova; Vyacheslav A. Starodubtsev (Высшее образование в России, 2016)
The article addresses the content of pedagogical support to successive stages (vocational guidance, propedeutics, identification, individualization, approbation, personification, and autonomy) of professional self-determination of higher school students aimed at shaping their subjective positions in the educational space. The model of the pedagogical support for professional self-determination and subjectivity has been elaborated, with the indicators of students' subjectivity. It is shown that the pedagogical support for vocational education in the educational space of a university can be a mechanism to harmonize the requirements of the modern and perspective labour market and personal needs of students.